Cognitive economics : new trends - Topol, Richard; Walliser, Bernard (Amsterdam ; Boston : Elsevier, 2007)
This book covers both the theoritical economist and the research worker.The publication of these studies will help to stimulate the exchange of scientific information and to reinforce international cooperation in the field of economics.
aia 04/09/13
Loan
Keywords: Economics; Cognitive science